Madonna of the Shadows (Madonna delle Ombre). - Stone, George Eathl (photographer):::Creator::::::::::::
The image depicts the sitting Madonna with Child with four saints on either side (note: the actual image diverges from the its title, alluding to "six" saints) (1387-1455).